Geometric and dosimetric accuracy and imaging dose of the real-time tumour tracking system of a gimbal mounted linac. Issue 5 (July 2015) - Garibaldi, Cristina; Russo, Stefania; Ciardo, Delia; Comi, Stefania; Seregni, Matteo; Fassi, Aurora; Piperno, Gaia; Ferrari, Annamaria; Pansini, Floriana; Bazani, Alessia; Ricotti, Rosalinda; Jereczek-Fossa, Barbara Alicja; et al.
Abstract Purpose To suggest a comprehensive testing scheme to evaluate the geometric and dosimetric accuracy and the imaging dose of the VERO dynamic tumour tracking (DTT) for its clinical implementation. Methods Geometric accuracy was evaluated for gantry 0° and 90° in terms of prediction (EP), mechanical (EM) and tracking (ET) errors for sinusoidal patterns with 10 and 20 mm amplitudes, 2–6 s periods and phase shift up to 1 s and for 3 patient patterns. The automatic 4D model update was investigated simulating changes in the breathing pattern during treatment. Dosimetric accuracy was evaluated with gafchromic films irradiated in static and moving phantom with and without DTT. The entrance skin dose (ESD) was assessed using a solid state detector and gafchromic films. Results The RMS of EP, EM, and ET were up to 0.8, 0.5 and 0.9 mm for all non phased-shifted motion patterns while for the phased-shifted ones, EP and ET increased to 2.2 and 2.6 mm. Up to 4 updates are necessary to restore a good correlation model, according to type of change. For 100 kVp and 1 mA s X-ray beam, the ESD per portal due to 20 s fluoroscopy was 16.6 mGy, while treatment verification at a frequency of 1 Hz contributed with 4.2 mGy/min. Conclusions The proposed testing scheme highlighted that the VERO DTT system tracks a moving target with high accuracy. The automatic update of the 4D model is a powerful tool to guarantee the accuracy of tracking without increasing the imaging dose.